Analysis of The Influence of Digital Marketing, Information and Technology Adoption and Use of Social Media on The Effectiveness of Tourism Promotion - Dharmawan, Donny; Luh Komang Candra Dewi; Hery Purnomo; Musran Munizu; Wadzibah Nas (Jurnal Sistim Informasi dan Teknologi, 2024)
This study aims to analyze the characteristics of digital marketing tools used in the communication process aimed at increasing the effectiveness of tourism management promotions. This study conducted document analysis, field observations and collected information from websites. The author used an analysis table to record and analyze data related to the appeal of tourist attractions and the marketing strategies used. The results of the analysis show that the implementation of effective digital strategies is very important in the management and promotion of tourist attractions. Websites and social networks must provide accurate and up-to-date information to build a positive image and make it easier for visitors to access and obtain various information needed regarding tourism trips. Accessibility features such as digital text and easy-to-understand navigation are very influential in attracting interest from tourists, while content provided with multilingual facilities affects the reach of tourists. Mobile applications increase the ease of booking and access to information. Digital marketing strategies that include social networks and multimedia content strengthen tourist visibility and engagement, ensure visitor experience and provide a positive destination image